Thrombin Generation in Acute Ischaemic Stroke - Ibrahim O. Balogun; Lara N. Roberts; Raj Patel; Rohan Pathansali; Lalit Kalra; Roopen Arya (Stroke Research and Treatment)
Introduction. Stroke remains a global leading cause of death and disability. Traditional description of plasma biology in the aftermath of acute ischaemic stroke favours development of hypercoagulability, resulting from complex interplay between plasma and endothelial factors. However, no single assay measures the overall global coagulation process. We postulate that thrombin generation would assist in identifying coagulation abnormalities after acute stroke. Aim. To investigate the coagulation abnormalities after acute ischaemic stroke using thrombin generation. Methods. We evaluated thrombin generation, measured with calibrated automated thrombography in stroke of different aetiological types (n=170) within 48 hours of symptoms onset (baseline) and in the second week (time 2) and in normal healthy volunteers (n=71). Results. Two-point thrombin generation assays showed prolonged lag time and time to peak at baseline (3.3 (2.9, 4.0) versus 3.6 (3.2, 4.7); p=0.005) and (3.3 (2.9, 4.0) versus 3.6 (3.2, 4.7); p=0.002), respectively, and at time 2 (3.5 (2.9, 4.2) versus 4.0 (3.1, 4.9); p=0.004) and (5.9 (5.3, 6.6) versus 6.8 (5.8, 7.7) p=0.05), respectively, in cardioembolic stroke (n=39), when compared to noncardioembolic stroke (n=117). The result was reproduced in multiple comparisons between acute ischaemic stroke subgroups and normal healthy volunteers. Endogenous thrombin potential and peak thrombin did not indicate hypercoagulability after acute ischaemic stroke, and thrombolytic therapy did not affect thrombin generation assays. Conclusion. Our findings suggest that thrombin generation in platelet poor plasma is not useful in defining hypercoagulability in acute ischaemic stroke. This is similar to observed trend in coronary artery disease and contrary to other hypercoagulable states.